2013
DOI: 10.1189/jlb.1112603
|View full text |Cite
|
Sign up to set email alerts
|

A leading role for the immune system in the pathophysiology of preeclampsia

Abstract: Preeclampsia syndrome is characterized by inadequate placentation, because of deficient trophoblastic invasion of the uterine spiral arteries, leading to placental hypoxia, secretion of proinflammatory cytokines, the release of angiogenic and antiangiogenic factors and miRNAs. Although immune-system alterations are associated with the origin of preeclampsia, other factors, including proinflammatory cytokines, neutrophil activation, and endothelial dysfunction, are also related to the pathophysiology of this sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
206
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(225 citation statements)
references
References 154 publications
0
206
1
7
Order By: Relevance
“…This localized oxygen and nutrient deprivation is associated with exaggerated trophoblast cell death (Jones & Fox 1980, Chua et al 1991, Knight et al 1998, Johansen et al 1999, Leung et al 2001, which has been suggested to directly contribute to the disease by releasing mediators of inflammation that promote endothelial activation and systemic maternal inflammation (Smarason et al 1993, Knight et al 1998, Redman & Sargent 2003. Although the etiology of PE is mostly unknown, a major hallmark is a generalized inflammatory response characterized by high cytokine levels, such as IL-1β, IL-6, IL-8 and tumor necrosis factor-α (Vince et al 1995, Mellembakken et al 2001, Laresgoiti-Servitje 2013, Harmon et al 2016. Because this inflammatory response usually occurs in the absence of microbial infection, PE primarily represents a sterile inflammation.…”
Section: Preeclampsiamentioning
confidence: 99%
“…This localized oxygen and nutrient deprivation is associated with exaggerated trophoblast cell death (Jones & Fox 1980, Chua et al 1991, Knight et al 1998, Johansen et al 1999, Leung et al 2001, which has been suggested to directly contribute to the disease by releasing mediators of inflammation that promote endothelial activation and systemic maternal inflammation (Smarason et al 1993, Knight et al 1998, Redman & Sargent 2003. Although the etiology of PE is mostly unknown, a major hallmark is a generalized inflammatory response characterized by high cytokine levels, such as IL-1β, IL-6, IL-8 and tumor necrosis factor-α (Vince et al 1995, Mellembakken et al 2001, Laresgoiti-Servitje 2013, Harmon et al 2016. Because this inflammatory response usually occurs in the absence of microbial infection, PE primarily represents a sterile inflammation.…”
Section: Preeclampsiamentioning
confidence: 99%
“…Although the vascular alterations occurring in pre-eclampsia are well established (43), the impact of immune components in its pathogenesis is less clear (7). Thus, we next interrogated the role of neutrophils in niT-cell induction in women with preeclampsia.…”
Section: Activated Neutrophils From Preeclamptic Pregnancies Fail To mentioning
confidence: 99%
“…Immune tolerance of the fetus relies on the concerted actions of hormones and cytokines, as well as cross-talk between innate and adaptive immune cells (6). Dysregulation of one or more of these components can lead to complications of pregnancy, including fetal growth restriction, preeclampsia, and recurrent miscarriages (7).…”
mentioning
confidence: 99%
“…Although there have been great advances in medicine, the frequency of this disease has not been successfully modified significantly (3). Currently, the etiology of this disease remains unknown, therefore, in order to explain its origin various theories have been raised, and within each of them the genetic origin, immune factor, endothelial dysfunction, increased oxidative stress, micronutrients deficiency, among others, can be mentioned (3)(4)(5)(6)(7)(8). During pregnancy, there is a normal increase in the production of reactive oxygen species (ROS); likewise, the antioxidant capacity is increased.…”
Section: Introductionmentioning
confidence: 99%